Evaluation of Fe isotope values as a provenance tool for chert artefacts from the north‐eastern United States. (8th May 2020) - Mathur, R.; Burns, J.; Powell, W.; Boryk, R.; Sheetz, B.; D'Amico, P.; Harney, P.
Abstract : Iron (Fe) isotope compositions of prehistoric stone tools and geological sources were compared to evaluate the robustness of this isotopic fingerprinting technique. Artefacts and source materials were collected from the Hatch site in central Pennsylvania, United States, where both veined chert (Bald Eagle chert) and stone tools coexist within several metres. Yellow artefacts ( δ 56 Fe = 0.38 ± 0.1, n = 7) and source materials ( δ 56 Fe = 0.42 ± 0.1, n = 8) isotopically matched within error. The source values also overlap yellow chert samples from three other Bald Eagle chert locations in the area. These values are different from six other chert locations in the north‐eastern United States. These data suggest that the Fe isotope composition of chert artefacts reflect distinct geological sources. To enhance the mechanical characteristics of the stone tools, the chert experienced heat treatment, which induced a phase shift of the Fe oxide mineral goethite to hematite. This phase shift changes the colour of the chert to red. The red chert artefacts and source material also have overlapping Fe isotope values, but are 0.2‰ higher than the initial yellow chert. Experimental work where cherts were heated with different clays shows that Fe exchange with site soils induces the +0.2 fractionation. These data demonstrate that predictable Fe isotope fractionation occurs during heating, resulting in isotopically distinct artefacts.